Flow-induced vibration : proceedings of the 7th International Conference on Flow-Induced Vibration - FIV 2000, Lucerne, Switzerland, 19-22 June 2000 /: proceedings of the 7th International Conference on Flow-Induced Vibration - FIV 2000, Lucerne, Switzerland, 19-22 June 2000. (2014) - Unknown
No abstract available